Digital hegemony and the reproduction of inequality: A Bourdieusian critical analysis of public policy in Indonesia - Indra Rahayu Ningsih; Grendi Hendrastomo (C-DISC, 2026)
Permendiktisaintek No. 39 of 2025 establishes higher education quality assurance standards emphasizing the use of “reliable” technology. While intended to improve educational quality, the policy may inadvertently widen digital and economic disparities among higher education institutions. This study examines how the policy reproduces inequalities in economic and cultural capital, symbolic violence, and cultural inferiority. Employing a qualitative critical policy analysis and regulatory discourse analysis, policy documents were analyzed using ATLAS.ti to examine the relationships among capital, quality standards, and mechanisms of domination. The findings reveal that the policy, despite its quality improvement agenda, has the potential to reinforce existing social and economic inequalities. The requirement for “reliable” technology converts economic capital into institutional advantages that shape accreditation outcomes. Moreover, the discourse of equality embedded in the policy obscures disparities in digital access and institutional capacity, while global quality standards are institutionalized as a form of doxa that marginalizes local values and knowledge. The study concludes that the policy is not value-neutral but reinforces social stratification within Indonesian higher education. It calls for more contextual, inclusive, and socially responsive quality assurance policies to promote equitable access and educational justice.